Competition between long time excitation and fading of thermoluminescence (TL) and optically stimulated luminescence (OSL). (August 2020) - Chen, R.; Lawless, J.L.; Pagonis, V.
Abstract: In the present work, we consider the filling and thermal emptying of traps and centers in a simple one-trap-one-recombination-center model in a small system such as a quartz grain in nature, when both the excitation and thermal release of electrons are very slow. Due to the nature of the very slow process, Monte Carlo simulations appear to be a very appropriate method. However, in parallel, we have applied an approximate analytical method and found practically the same results although the Monte Carlo results showed some small fluctuations due to the statistical nature of the procedure. This is in line with the experimental results which are also expected to have statistical fluctuations. The main result found is that after a long enough time, measured in hundreds or thousands years or more, the filling of the trap reaches a plateau which, depending on the parameters, may be very significantly smaller than the concentration of the trap in question. This equilibrium value is the same if we start from very low, e.g. zero concentration or very high, above the equilibrium value. This plateau level depends strongly on the relevant parameters. However, comparing simulations with activation energies of 1.2 eV and 1.3 eV shows strong dependence of the plateau level on the energy. Similarly, we can expect strong dependence on the temperature at which the sample is held. The results reached here and shown in Figs. 1–4 are based on the simplest OTOR model, but similar results of approaching a plateau level which are not due to the saturation of traps may occur in more complex systems as is demonstrated by simulations based on the Bailey model for quartz which includes several traps and centers. Highlights: Competition between excitation and fading of TL and OSL. Monte Carlo simulation of excitation and fading of trap filling. Reaching plateau level in the Bailey model for quartz. Temperature and activation energy dependence of the equilibrium level.